Kiai Kharismatik dan Hegemoninya (Telaah Fenomena Habib Syech bin Abdul Qadir Assegaf) - Ferri Wicaksono (Jurnal Pemerintahan dan Politik, 2019)
Abstract This paper discusses the pattern of kiai hegemony as a charismatic leader. Kiai have a strategic position, are very respectable, and even have a big influence on the development of a community. The author examines the phenomenon of Habib Syech bin Abdul Qadir Assegaf as one of the charismatic kiai. Kiai is not a person who is experienced and has professional skills, but is socially proven to be able to spearhead the process of social change in society. The functionalist perspective presented by William F. Ogburn the author uses as an approach in interpreting the kiai's charismatic leadership. This perspective considers social change as something that can disrupt the balance of society. Kiai not only restricts the flow of culture, but the kiai seeks to spearhead change. The main finding in this paper is that compliance that is formed from a charismatic kiai is able to consciously obey his followers and without coercion. Kiai not only restricts the flow of culture, but the kiai tries to spearhead changes. On the other hand Habib Syech bin Abdul Qadir Assegaf tends to create restrictions on relations to a political party activity. In a functionalist perspective, change is integrated in culture. The culture of sholawatan that has grown very strong among the NU community, is another supporting aspect in the creation of charismatic permanence Habib Syech bin Abdul Qadir Assegaf as a Kiai. Charismatic leadership is raised on the emotional involvement of an individual in identifying the psychological individual of his followers in an effective way, which leads to cultural constancy adopted by certain community groups.Keywords : kiai, leadership, charismatic, hegemonyAbstrak Tulisan ini membahas tentang pola hegemoni kiai sebagai pemimpin kharismatik. Kiai mempunyai kedudukan strategis, sangat terhormat, bahkanberpengaruh besar pada perkembangan suatu komunitas. Penulis melakukan telaah terhadap fenomena Habib Syech bin Abdul Qadir Assegaf sebagai salah seorang kiai kharismatik. Kiaibukanlah sosok yang berpengalaman dan memiliki kemampuan profesional, tetapi secara sosial terbukti mampu memelopori proses perubahan sosial dalam masyarakat. Perspektif fungsionalis yang disampaikan oleh William F. Ogburn penulis gunakan sebagai sebuah pendekatan dalam memaknai kepemimpinan kharismatik kiai.Perspektif ini menganggap perubahan sosial sebagai suatu hal yang dapat mengacaukan keseimbangan masyarakat.Kiai bukan hanya membatasi arus budaya yang masuk, namun kiai berupaya memelopori perubahan Temuan utama didalam tulisan ini adalah kepatuhan yang terbentuk dari kharismatik seorang kiai mampu menghegemoni pengikutnya dengan sadar dan tanpa suatu paksaan. Kiai bukan hanya membatasi arus budaya yang masuk, namun kiai berupaya memelopori perubahan. Disisi lain Habib Syech bin Abdul Qadir Assegafcenderung menciptakan pembatasan hubungan terhadap suatu aktivitas partai politik. Dalam perspektif fungsionalis perubahan terintegrasi dalam kebudayaan.Budaya sholawatan yang sudah tumbuh sangat kuat dikalangan masyarakat NU, menjadi aspek pendukung lain dalam penciptaan kelanggengan kharismatik Habib Syech bin Abdul Qadir Assegafsebagai seorang Kiai. Kepemimpinan kharismatik dimunculkan atas keterlibatan emosional seseorang individu dalam mengidentifikasi psikologis individu pengikutnya dengan cara efektif, yakni mengarah pada keajegan budaya yang dianut oleh kelompok masyarakat tertentu.Kata kunci : kiai, kepemimpinan, kharismatik, hegemoni